High or low calcium intake increases cardiovascular disease risks in older patients with type 2 diabetes - Huang, Jui-Hua (BioMed Central, 2014)
BACKGROUND: We investigated the effects of dietary calcium (Ca) and magnesium (Mg) intakes on cardiovascular disease risks in older patients with diabetes. METHODS: In this cross-sectional study, 197 patients with type 2 diabetes aged 65 years and above were recruited. The 24-h dietary recalls and 1-week self-reported typical dietary intake patterns were collected. The Ca and Mg intakes of <67% of the recommended dietary allowance (RDA), 67%–100% of RDA, and >100% of RDA were defined as low, moderate, and high Ca and Mg intakes, respectively. Anthropometric measurements were determined and biochemical analysis of blood and urine was performed. RESULTS: Our data indicated that 60.9% and 87.3% of our patients were Ca and Mg intakes below RDA, respectively. Patients whose Ca intake was high or low (81.2%) had significantly higher C-reactive protein (CRP) than those whose Ca intake was moderate (p = 0.043). Furthermore, patients whose Mg intake was low (87.3%) had significantly higher CRP than that of those who took adequate Mg (p = 0.025). The dietary Ca:Mg intake ratios were highly correlated with CRP, platelet counts, and red blood cell distribution (p < 0.05). A dietary Ca:Mg intake ratio of 2.0–2.5 was significantly correlated to lower CRP levels (p = 0.013). CONCLUSIONS: High or low calcium intake increases cardiovascular disease risks. We suggest that “moderate” intake of 402–600 mg Ca/day (approximately 67%–100% of Taiwan RDA for Ca) and adequate Mg intake (or meeting RDA for Mg) with Ca:Mg intake ratio of 2.0–2.5 are important for reducing cardiovascular disease risks in older patients with diabetes.